1982
DOI: 10.1177/004051758205200806
|View full text |Cite
|
Sign up to set email alerts
|

Capsule-Producing Coryneform Bacteria Associated with Stickiness in Cotton

Abstract: Sticky cotton samples received at the Textile Research Center of Texas Tech University for processing had a significantly higher proportion of white colonies (many of which were coryneform bacteria) than non-sticky cotton samples, although the same kinds of organisms were present on both kinds of cottons. Four representative strains of coryneform bacteria were isolated from samples of both sticky and non-sticky cotton and examined for their ability to produce extracellular carbohydrates. When grown on thioglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Wyatt and Heintz [37] reported that possibly capsule-forming coryneform bacteria contribute to stickiness when they constitute a significant population of the bacteria present on cotton. Since previous investigators [5,8,9,25,28] reported that carbohydrates TABLE il.…”
Section: Resultsmentioning
confidence: 99%
“…Wyatt and Heintz [37] reported that possibly capsule-forming coryneform bacteria contribute to stickiness when they constitute a significant population of the bacteria present on cotton. Since previous investigators [5,8,9,25,28] reported that carbohydrates TABLE il.…”
Section: Resultsmentioning
confidence: 99%